Can we predict the clinical outcome of arthroscopic partial meniscectomy? A systematic review. Issue 8 (28th November 2017) - Eijgenraam, Susanne M; Reijman, Max; Bierma-Zeinstra, Sita M A; van Yperen, Daan T; Meuffels, Duncan E
Abstract : NHS-Prospero registration number: 42016048592 Objective: In order to make a more evidence-based selection of patients who would benefit the most from arthroscopic partial meniscectomy (APM), knowledge of prognostic factors is essential. We conducted a systematic review of predictors for the clinical outcome following APM. Design: Systematic review Data sources: Medline, Embase, Cochrane Central Register, Web of Science, SPORTDiscus, PubMed Publisher, Google Scholar Inclusion criteria: Report an association between factor(s) and clinical outcome; validated questionnaire; follow-up >1 year. Exclusion criteria: <20 subjects; anterior cruciate ligament-deficient patients; discoid menisci; meniscus repair, transplantation or implants; total or open meniscectomy. Methods: One reviewer extracted the data, two reviewers assessed the risk of bias and performed a best-evidence synthesis. Results: Finally, 32 studies met the inclusion criteria. Moderate evidence was found, that the presence of radiological knee osteoarthritis at baseline and longer duration of symptoms (>1 year) are associated with worse clinical outcome following APM. In addition, resecting >50% of meniscal tissue and leaving a non-intact meniscal rim after meniscectomy are intra-articular predictive factors for worse clinical outcome. Moderate evidence was found that sex, onset of symptoms (acute or chronic), tear type or preoperative sport level are not predictors for clinical outcome. Conflicting evidence was found for the prognostic value of age, perioperative chondral damage, body mass index and leg alignment. Summary/conclusion: Long duration of symptoms (>1 year), radiological knee osteoarthritis and resecting >50% of meniscus are associated with a worse clinical outcome following APM. These prognostic factors should be considered in clinical decision making for patients with meniscal tears.